Pengaruh Disiplin Belajar dan Minat Siswa terhadap Hasil Belajar Pendidikan Agama Islam di SMA N 1 Panyabungan Selatan Kabupaten Mandailing Natal - Rohimah Nur Nasution (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This research in a type of quantitative research. The population in this study were all students of class X and XI in SMAN 1 Panyabungan Selatan amounting to 152 people. Sampling is done by sampling technique used is proportional stratified random sampling. The number of samples in this study were 60 students. The instrument used was a questionnaire. Data were analyzed using multiple linear regression analysis techniques.The findings of this study indicate that 1) The influence of learning discipline on student learning uotcomes in SMAN 1 Panyabungan Selatan. The value of regression coefficient is 25%. Positive coefficient means that there is a positive influence between learning discipline an student learning outcomes, the better the discipline of student learning, the better student learning uotcomes, 2) The influence of student learning interest on learning outcomes in SMAN 1 Panyabungan Selatan. Based on regression coefficient of 46% . Positive coefficient means that there is positive influence between learning interest an student learning outcomes, the better the discipline of student learning, the better student learning uotcomes, 3) The influence of learning discipline and student interest in learning outcomes of Islamic religious education in SMAN 1 Panyabungan Selatan. Learning discipline and interest in learning together have a positive and significant outcomes in SMAN 1 Panyabungan Selatan.